Outcomes of Early Versus Delayed Anemia Treatment in Nondialysis-Dependent CKD - Kouji Kawai; Manabu Ishii; Yoshimasa Kokado; Takashi Horikawa; Junichi Hoshino (Kidney International Reports)
Introduction: The association of hemoglobin level at treatment initiation with renal and cardiovascular outcomes in patients with anemia in nondialysis-dependent (NDD) chronic kidney disease (CKD) is unclear. Methods: This retrospective cohort study utilized 2 Japanese databases (Medical Data Vision Co. Ltd., Tokyo, Japan [MDV]; and Real World Data Co. Ltd, Kyoto, Japan [RWD]). Patients initiated on long-acting erythropoiesis-stimulating agent (ESA) treatment were divided into early (hemoglobin levels ≥9.0 g/dl) and delayed (<9.0 g/dl) treatment groups. The primary outcome was a renal composite (renal replacement therapy, ≥50% estimated glomerular filtration rate [eGFR] reduction, eGFR <6.0 ml/min per 1.73 m2, and all-cause mortality), and secondary outcomes were a cardiovascular composite (hospitalization by ischemic heart disease, including myocardial infarction, hospitalization by stroke and heart failure, and cardiovascular death) and components of the composite outcomes. Results: After propensity score matching, 1472 (MDV) and 1264 (RWD) patients were evaluated. Delayed treatment was not associated with a risk of the renal composite outcome (MDV: hazard ratio [HR]: 1.15, 95% confidence interval [CI]: 0.99–1.33; RWD: HR: 1.08, 95% CI: 0.92–1.28). However, delayed treatment was associated with higher risks of the cardiovascular composite outcome (MDV: HR: 1.47, 95% CI: 1.16–1.84; RWD: HR: 1.34, 95% CI: 1.09–1.64), heart failure (MDV: HR: 1.50, 95% CI: 1.13–2.00; RWD: HR: 1.53, 95% CI: 1.20–1.96) and all-cause mortality (MDV: HR: 1.83, 95% CI: 1.32–2.54; RWD: HR: 1.64, 95% CI: 1.21–2.22). Conclusion: Although the risk of renal events was not increased following delayed treatment of anemia in patients with NDD-CKD, the risks of cardiovascular events and all-cause mortality were increased, suggesting the importance of early intervention before hemoglobin falls below 9.0 g/dl.